Exploring the Determinants of Fuel wood Use in Western Hill Nepal: An Econometric Analysis - Bhattarai, Lekh Nath (Economic Literature, 2016)
Forest resources use at the household level may be determined by socio-economic as well as physical factors adjacent to the users. This paper is based on the study conducted by the author to explore the determinants of fuelwood use at household level with field survey data from the samples of households along the stretch of middle hills in Arghakhanchi District, west Nepal. The findings of multiple regression analysis clearly suggest that the physical quantity of fuelwood used per capita is significantly influenced by the households’ socio-economic indicators such as income, household size, landholding, and domestic animal holding and to some extent caste and ethnicity. Similarly, the distance to nearest forest is also an important predictor, exhibiting negative and significant effect. But the net effects of per capita landholding on per capita fuel wood collected from public forest appeared to be negative. It is not only an indication of higher dependency of poor on public forests but also an evidence of manifestation of their deprivation. It leads to imply a fact that the use of forest resource such as fuelwood can be reduced increasing the socio-economic status of the users. Economic Literature, Vol. XI (26-34), June 2013